What women want? A scoping survey on women's knowledge, attitudes and behaviours towards ovarian reserve testing and egg freezing. (October 2017) - O'Brien, Yvonne; Martyn, Fiona; Glover, Louise E.; Wingfield, Mary B.
Abstract: Objective: We aimed to investigate women's knowledge, attitudes and behaviours towards ovarian reserve testing and egg freezing for non-medical reasons in the general population. Study design: This was a cross-sectional survey study of 663 women aged 18–44 years which assessed female perception of ovarian reserve testing and oocyte cryopreservation. An online forum was used to deliver the survey through the use of two social media sites. Participants were recruited through the technique of "snowballing", whereby existing study subjects recruited others from among their acquaintances. The data collected was analyzed using SPSS to explore descriptive statistics and frequencies relating to the participants' knowledge, attitudes and behaviour towards the practices of ovarian reserve testing and oocyte cryopreservation. Categorical variables were analyzed using Chi-squared; a p -value of <0.05 was considered significant. Results: A majority (60%) of women surveyed had knowledge of ovarian reserve testing. 64.8% would be interested in having testing performed. Younger women (<30 years of age) were more interested in checking their ovarian reserve (75.8% vs. 59.1%, p < 0.0001). Single women were also more likely to be interested, (73.6% v's 62.1%, p = 0.022). 89.7% of women surveyed were aware of oocyte cryopreservation. 72.2% agreed that they would consider freezing their eggs to preserve fertility. There was no significant difference in the numbers of single women compared to women in a relationship who would consider egg freezing to preserve fertility (75.7% v's 71.2%, p = 0.347, or in younger (<30 years) compared to older women, (74.7% v's 71.1%, p = 0.387). A majority (62.1%) of study participants believed that it is a woman's right to postpone pregnancy for social reasons and to freeze her eggs, with no significant difference in options noted between younger and older women. Conclusions: Knowledge of ovarian reserve testing and oocyte cryopreservation for non-medical reasons were higher than in previous studies, possibly reflecting increasing awareness of these issues among the general public. Additionally, we demonstrated that the women, in our study, were very open to the use of these modern technologies in an attempt to avoid unintended childlessness.